Assessment of anthropogenic impacts on water quality in Gebeng industrial area, Kuantan, Pahang - Siti Asmaul , Husna Salleh (2014)
Due to fast development in Malaysia, the numbers of industrial estates are increasing. Gebeng are the main industrial area in Pahang. The Tunggak River which is adjacent to the area, are receiving lots of industrial wastes. This study was done to assess the water quality based on National Water Quality Standard (NWQS) and Malaysian Water Quality Index (WQI) and the factors that affect the water quality. Sampling was done for three months at five stations. The chemical, and biological parameters were measured. Those parameters are temperature, dissolved oxygen (DO), pH, turbidity, biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), E.Coli, total coliform, ammoniacal nitrogen (NH3 N) and heavy metal. From the result, the water quality in the study area is in Class ifi. The high temperatures were resulting to the low value of dissolve oxygen. High concentrations of ammonia were detected in all sampling station indicating that it was rich with industrial wastes. The high concentration of ferum was detected at station 5. The types of industries involved were one of the factors affecting water quality in the study area. In summary, the water quality in the Gebeng area has been degraded and required more attention from all parties involved.